24-h variation in soil respiration after a long dry season in a Sudano-Sahelian region (Scientia Agricola, 2015)
Soil respiration is a major component of the global carbon cycle which links ecosystems and the atmosphere. To evaluate the reaction of soil respiration after wetting, during a dry period, soil respiration and associated environmental factors were measured over a 24-h period, during the dry season in North Cameroon after wetting the soil. Over 24-h, soil respiration rates followed a quadratic curve during the day coming close to linear at night, while soil temperature and moisture together explained at least 73 % of the variations during the 24-h observed. These soil respiration rates increased during the morning, peaked between 11h00 and 13h00 and then decreased gradually to the minimum around 06h00. These observations were used to propose a method for estimating mean daytime and nighttime soil respiration after wetting the soil. The method proposed in this study has the advantage of being based on a small number of measurements and is, therefore, easier to implement for monitoring 24-h soil respiration after the first rains following a long dry period.